LES Of intermittency in a turbulent round jet with different inlet conditions - Ranga Dinesh, K. K. J.; Savill, Mark A.; Jenkins, Karl W.; Kirkpatrick, M. P. (Elsevier, 2010)
Large eddy simulation (LES) is a promising technique for accurate prediction of turbulent free shear flows in a wide range of applications. Here the LES technique has been applied to study the intermittency in a high Reynolds number turbulent jet with and without a bluff body. The objective of this work is to study the turbulence intermittency of velocity and scalar fields and its variation with respect to different inlet conditions. Probability density function distributions (pdf) of instantaneous mixture fraction and velocity have been created from which the intermittency has been calculated. The time averaged statistical results for a round jet are first discussed and comparisons of velocity and passive scalar fields between LES calculations and experimental measurements are seen to be good. The calculated probability density distributions show changes from a Gaussian to a delta function with increased radial distance from the jet centreline. The effect of introducing a bluff body into the core flow at the inlet changes the structure of pdfs, but the variation from Gaussian to delta distribution is similar to the jet case. However, the radial variation of the intermittency indicates differences between the results with and without a bluff body at axial locations due the recirculation zone created by the bluff body.
Keywords: Intermittency; Probability density function; Turbulence; Recirculation; LES